Parental Migration, Investment in Children, and Children's Non-cognitive Development: Evidence from Rural China - Hanchen Jiang; Xi Yang (Global Labor Organization (GLO), 2019)
Many children worldwide are left behind by parents who are migrating for work. While previous literature has studied the effect of parental migration on children's educational outcomes and cognitive achievements, this study focuses on how parental migration affects children's non-cognitive development. We use longitudinal data of children in rural China and adopt labor market conditions in destination provinces as instrumental variables for parental endogenous migration choice. We find that parental migration has a significant negative effect on children's non-cognitive development. Differentiating inter- and intra-provincial migrations suggests that the negative effect of parental migration is mainly driven by inter-provincial migrations. We test four different mechanisms of how parental migration affects child development including parental financial inputs, parental time inputs, household bargaining, and children's own time input. Our results provide insights into the relative importance of different mechanisms in determining the effect of parental migration on children's non-cognitive skill formation.
Keywords: J12; J13; J24; J61; R23; 330; Left-behind Children; Parental Migration; Parental Input; Non-cognitive Development; China